DIVERSITAS, POLA SEBARAN, DAN KELIMPAHAN CAPUNG DI PULAU LOMBOK “LITERATUR REVIEW” - Lalu Amrullah (LPPM, Institut Teknologi dan Kesehatan Aspirasi, 2026)
Background: Dragonflies (Odonata) play an important role as bioindicators of aquatic environments and ecosystem health. Lombok Island, with its diverse topographic features from coastal to mountainous areas (such as Mount Rinjani), holds significant potential for Odonata diversity. However, anthropogenic pressures threaten their natural habitats, necessitating a comprehensive review of their diversity and distribution.Results: This study is a qualitative descriptive research using a literature review design.Conclusion: The results of the literature review from various studies indicated that Lombok Island possesses high dragonfly diversity, consisting of tens of species from the suborders Anisoptera and Zygoptera. The distribution pattern is heavily influenced by environmental factors such as water temperature, altitude, and vegetation cover. The abundance of dragonflies is highest in undisturbed lotic and lentic ecosystems with clean water conditions.